Ethno-chemistry: Relevance Analysis of Electron Valence Subject Material to Sasak Local Wisdom as a Chemistry Learning Resource - Umam, Kholid Khairul; Wahyudiati, Dwi (Hydrogen: Jurnal Kependidikan Kimia, 2023)
The lack of learning resources in the form of teaching materials is one of the problems found in the chemistry learning process, both within the scope of high schools and universities so that the development of contextual teaching materials is very important to do as an implementation of the ethno-chemistry approach in education. The purpose of this research is to explore and reveal the wisdom or local wisdom of the Sasak community, which is developed into teaching materials. This research approach uses a qualitative approach with data collection techniques using interviews, literature studies and documentation methods. A qualitative research approach with interview techniques, literature studies, and documentation methods was used to collect information in the form of individual views, theoretical understandings, and historical data related to the research topic, with the aim of gaining in-depth insights, contextual understanding, and theoretical support needed in the analysis and explanation of the phenomenon under study. The data obtained Analyze by Miles and Huberman qualitative analysis. Research subjects include community leaders, chemical content experts, and reading books relevant to the research. Based on the research findings. It is concluded that Sasak Begibung Culture can be used as a source of learning chemistry through integrating Sasak Begibung culture with valence electron material. Thus, the implementation of this research can be used as a reference in the development of contextualized chemistry teaching materials so that lessons become more meaningful and effective.